2018
DOI: 10.1055/a-0770-0994
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and In Vitro Anti-inflammatory Activity of C20 Epimeric Ocotillol-Type Triterpenes and Protopanaxadiol

Abstract: Ginseng is a perennial herb that contains various medicinal substances. The major active constituents of ginseng are ginsenosides, which have multifarious biological activities. Some pharmacological activities are closely dependent on the stereoisomers derived from the configuration at C20. In this study, the in vitro anti-inflammatory activity of C20 epimeric ocotillol-type triterpenes (2, 3, 9, and 10) and protopanaxadiol [20(S/R)-protopanaxadiol] were investigated. Epimers 2 and 3 were prepared starting fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 26 publications
0
21
0
Order By: Relevance
“…Both P. notoginseng saponins and ginseng total saponins have significant antidepressant effects on LPS‐induced murine CD‐1 mouse models (An Kang et al, ; A. Kang et al, ) by reducing the mRNA levels of IL‐1β, IL‐6, TNF‐α, and indoleamine 2,3‐dioxygenase in the hippocampus. Moreover, PPD was recently found to protect against cerebral ischemia by inhibit inflammatory cytokine release in vitro (J. Zhang et al, ). Thus, it has been speculated that PPD exerts antidepressant‐like effects via the inhibition of the immune‐inflammatory, oxidative, and nitrosative stress pathways in the aetiology of depression, and this hypothesis needs to be explored in our future research.…”
Section: Discussionmentioning
confidence: 99%
“…Both P. notoginseng saponins and ginseng total saponins have significant antidepressant effects on LPS‐induced murine CD‐1 mouse models (An Kang et al, ; A. Kang et al, ) by reducing the mRNA levels of IL‐1β, IL‐6, TNF‐α, and indoleamine 2,3‐dioxygenase in the hippocampus. Moreover, PPD was recently found to protect against cerebral ischemia by inhibit inflammatory cytokine release in vitro (J. Zhang et al, ). Thus, it has been speculated that PPD exerts antidepressant‐like effects via the inhibition of the immune‐inflammatory, oxidative, and nitrosative stress pathways in the aetiology of depression, and this hypothesis needs to be explored in our future research.…”
Section: Discussionmentioning
confidence: 99%
“…Comment 20(S)-ocotillol-type saponin sharing a tetrahydrofuran ring and a dammarane skeleton, are a class of rare ginsenosides [5], which was achieved by base degradation from leaves and stems of Panax quinquefolius and they play a key role in neuroprotection [6], antibacterial [7] and antitumor activities [8]. It has been reported to possess good potential for myocardial ischemia and myocardial injury [9,10].…”
Section: Methodsmentioning
confidence: 99%
“…The ocotillol-type triterpenes are a rare kind of ginsenosides characterized by a tetrahydrofuran ring on the side chain [8][9][10][11]. It has been reported that ocotillol-type triterpenes have antibacterial, antioxidative, anti-inflammatory, neuroprotective and cardioprotective properties [12][13][14][15][16]. It is worth noting that the stereoconfiguration of the C-24 position may influence their stereoselectivity in pharmacological action and pharmacokinetics [17].…”
Section: Commentmentioning
confidence: 99%